From pandemic to endemic: assessing the impact of COVID-19 history and socio-demographic factors on quality of life in tuberculosis patients - Mitroi, Denisa Maria; Balteanu, Mara Amalia; Zlatian, Ovidiu Mircea; Toma, Claudia Lucia; Catana, Oana Maria; Mirea, Adina Andreea; Camen, Georgiana; Biciusca, Viorel; Cioboata, Ramona (Frontiers in Medicine, 2025)
BackgroundTuberculosis (TB) and COVID-19 are major global health concerns, and their interaction, particularly regarding socio-demographic factors, remains insufficiently explored. This study assessed the impact of prior confirmed COVID-19, alongside age, education, smoking, gender, and marital status, on TB relapse risk and quality of life (QOL) among TB patients in South-Western Romania.MethodsA cross-sectional analysis was performed on 763 bacteriologically confirmed TB patients enrolled between October 2022 and January 2025. Participants provided socio-demographic and clinical information and completed the WHOQOL-BREF questionnaire. Binary logistic regression was used to identify predictors of TB relapse, while structural equation modeling (SEM) assessed factors influencing QOL.ResultsPatients with a confirmed history of COVID-19 exhibited a twofold increase in TB relapse risk (OR = 2.08, p = 0.003). Age was a strong predictor, with individuals aged 36–60 years and those >60 years showing over fivefold (OR = 5.08, p < 0.001) and nearly fourfold (OR = 3.96, p = 0.004) increases in relapse risk, respectively. Smoking further increased relapse odds by 76% (OR = 1.77, p = 0.009). Conversely, secondary and tertiary education significantly reduced relapse risk (OR = 0.48, p = 0.002; OR = 0.46, p = 0.006). SEM revealed that COVID-19 history had a pronounced negative impact on QOL (β = −0.51, p < 0.001), while marital status (β ≈ 0.09, p = 0.022) and education (β ≈ 0.18, p < 0.001) were positively associated with QOL.ConclusionCOVID-19, advanced age, and smoking significantly elevate TB relapse risk and detrimentally affect QOL, whereas higher education appears protective. Integrated interventions addressing COVID-19 prevention, smoking cessation, and socio-economic support are essential to improve TB outcomes and patient quality of life.